Complementarity between Product and Process innovation in a Monopoly Setting - Andrea Mantovani (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2005)
We study complementarity between product and process innovation in a monopoly setting. First we consider the possibility for the firm to alternatively invest only along one of the two directions and compare the incentives of process vs product innovation. Then we allow the firm to invest simultaneously in both activities, showing that both investment levels as well as the profit are higher than in case of individual investment. Product and process innovations are then complementary and the firm always prefers a simultaneous adoption.
Keywords: 330; Innovation; Technischer Fortschritt; Investitionsentscheidung; Monopol; Theorie